2021
DOI: 10.1111/ffe.13570
|View full text |Cite
|
Sign up to set email alerts
|

On the use of different diametral compression cracked disc shape specimens for introducing mode III deformation

Abstract: Due to the difficulties of applying torsional loads to introduce mode III effects, there are few studies for investigating mixed mode I/III fracture in brittle materials. In this paper using three novel single or double edge-cracked diametral compression disc shape specimens, complete ranges of mixed mode I/III are introduced. Fracture factors of the compressed disc specimens with different pre-notch shapes are determined numerically for a wide range of notch depth and notch inclination angles. The ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…Furthermore, based on prior fracture studies of rocks, it has been demonstrated that the geometry, material type, crack type, and loading conditions can significantly affect fracture behavior and fracture properties such as fracture toughness 47–59 . Similarly, the results obtained on the basis of experimental research indicated that the size of the FPZ is also limited by a number of factors, such as the geometry and loading type of the cracked specimen as well as the size of the test sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, based on prior fracture studies of rocks, it has been demonstrated that the geometry, material type, crack type, and loading conditions can significantly affect fracture behavior and fracture properties such as fracture toughness 47–59 . Similarly, the results obtained on the basis of experimental research indicated that the size of the FPZ is also limited by a number of factors, such as the geometry and loading type of the cracked specimen as well as the size of the test sample.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on prior fracture studies of rocks, it has been demonstrated that the geometry, material type, crack type, and loading conditions can significantly affect fracture behavior and fracture properties such as fracture toughness. [47][48][49][50][51][52][53][54][55][56][57][58][59] Similarly, the results obtained on the basis of experimental research indicated that the size of the FPZ is also limited by a number of factors, such as the geometry and loading type of the cracked specimen as well as the size of the test sample. For example, as reported by Moazzami et al, 60 the length of the FPZ for the single edge notch bending (SENB) marble specimen is different from that of the SCB sample under the same loading condition.…”
Section: Examinations Of the Validity And Potential Contributing Comp...mentioning
confidence: 98%
“…Aliha and Fattahi Amirdehi 38 and Xiongzhou et al 39 used edge crack semicircular bend (SCB) samples to examine the fracture behavior/toughness of asphalt mixtures and claimed that they were suitable for laboratory setup and involved an easy implementation method to evaluate the fracture characteristics 40,41 . Edge notched disk bend (ENDB) that was first presented by Aliha et al 42 is the type that has recently been popular with researchers due to its simple geometry, ease of preparation, and easy laboratory setup, which help evaluate the specimen behavior under different single and combined loading modes 43–52 . Studying the effects of fibers on the concrete fracture toughness, Aliha et al 15 concluded that using forta‐ferro fibers in concrete increased the cracking resistance of ENDB specimens under pure loading modes I and III.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Edge notched disk bend (ENDB) that was first presented by Aliha et al 42 is the type that has recently been popular with researchers due to its simple geometry, ease of preparation, and easy laboratory setup, which help evaluate the specimen behavior under different single and combined loading modes. [43][44][45][46][47][48][49][50][51][52] Studying the effects of fibers on the concrete fracture toughness, Aliha et al 15 concluded that using forta-ferro fibers in concrete increased the cracking resistance of ENDB specimens under pure loading modes I and III. They also believed that the fiber effect on the concrete fracture toughness was more in the tearing mode than in the tensile mode.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods can be used for the measurement of the mode I fracture toughness of geomaterials, including semicircular bend (SCB), chevron bend (CB), short rod (SR), and cracked chevron notched Brazilian disc (CCNBD) methods 19,20 . Owing to the difficulty in cutting/halving rocks, some scholars manage to use full circular specimens for measuring the fracture toughness of rock 21–23 . Compared with other testing methods, SCB tests have several advantages, including simple test procedures and experimental setup, more efficient usage of testing materials, and excellent repeatability, 24 and thus have been widely employed in a routine mix design and quality screening.…”
Section: Introductionmentioning
confidence: 99%